Family and Politics in an Archipelagic Province: The Moreno Dynasty in Postwar Romblon, 1949–1969 - Esquejo, Kristoffer R. (Kasarinlan: Philippine Journal of Third World Studies; Vol 33 No 2 (2018): Localities, 2020)
Through documentary sources and oral interviews, this article examines the vital role played by Romblon’s distinct features as an archipelagic province on its local politics, particularly the rise and fall of the Moreno dynasty. The elder brother was Florencio Moreno, a government civil engineer who served as Romblon’s congressman and was later appointed as Department of Public Works and Communications (DPWC) secretary under the Magsaysay and Garcia administrations. The younger brother was Jose D. Moreno, a wartime military doctor who succeeded his elder brother as Romblon’s congressman for three terms. From 1949 to 1969, the Moreno dynasty monopolized the said position, effectively bringing progress and pride of place to their constituents and figuratively putting Romblon on the Philippine map. While the brothers represent the emergence of professional politicians in Philippine postwar politics, their respective political careers were still largely restricted by the combined factors of geography, demography, and kinship dynamics of their home province. As a result, a sibling rivalry erupted which ultimately ended not only their political heyday but also shattered their economic interests.
Keywords: Moreno Dynasty; Kinship Politics; Public Works; Health; Romblon